Modeling the molecular gas content and CO-to-H2 conversion factors in low-metallicity star-forming dwarf galaxies - Ramambason, Lise; Lebouteiller, V.; Madden, S. C.; Galliano, F.; Richardson, C. T.; Saintonge, A.; Looze, I. De; Chevance, Mélanie; Abel, N. P.; Hernandez, S.; Braine, J. (Astronomy and astrophysics, 2024)
Context. Low-metallicity dwarf galaxies often show no or little CO emission, despite the intense star formation observed in local samples. Both simulations and resolved observations indicate that molecular gas in low-metallicity galaxies may reside in small dense clumps, surrounded by a substantial amount of more diffuse gas that is not traced by CO. Constraining the relative importance of CO-bright versus CO-dark H2 star-forming reservoirs is crucial to understanding how star formation proceeds at low metallicity. Aims. We test classically used single component radiative transfer models and compare their results to those obtained on the assumption of an increasingly complex structure of the interstellar gas, mimicking an inhomogeneous distribution of clouds with various physical properties. Methods. Using the Bayesian code MULTIGRIS, we computed representative models of the interstellar medium as combinations of several gas components, each with a specific set of physical parameters. We introduced physically motivated models assuming power-law distributions for the density, ionization parameter, and the depth of molecular clouds. Results. This new modeling framework allows for the simultaneous reproduction of the spectral constraints from the ionized gas, neutral atomic gas, and molecular gas in 18 galaxies from the Dwarf Galaxy Survey. We confirm the presence of a predominantly CO-dark molecular reservoir in low-metallicity galaxies. The predicted total H2 mass is best traced by [C II]158 μm and, to a lesser extent, by [C I] 609 μm, rather than by CO(1-0). We examine the CO-to-H2 conversion factor (αCO) versus metallicity relation and find that its dispersion increases significantly when different geometries of the gas are considered. We define a “clumpiness” parameter that is anti-correlated with [C II]/CO and explains the dispersion of the αCO versus metallicity relation. We find that low-metallicity galaxies with high clumpiness parameters may have αCO values as low as the Galactic value, even at low metallicity. Conclusions. We identify the clumpiness of molecular gas as a key parameter for understanding variations of geometry-sensitive quantities, such as αCO. This new modeling framework enables the derivation of constraints on the internal cloud distribution of unresolved galaxies, based solely on their integrated spectra.